In Vitro Fertilization and Risk for Hypertensive Disorders of Pregnancy: Associations With Treatment Parameters. Issue 10 (October 2020) - Luke, Barbara; Brown, Morton B.; Eisenberg, Michael L.; Callan, Caitriona; Botting, Beverley J.; Pacey, Allan; Sutcliffe, Alastair G.; Baker, Valerie L.
Abstract : (Abstracted from Am J Obstet Gynecol 2020;222:350.e1–350.e13) With an increasing proportion of pregnancies being conceived using assisted-reproductive technology, important changes to in vitro fertilization (IVF) such as the use of cryopreserved oocytes or embryos have been made. It is now established that adverse maternal and infant perinatal outcomes are associated with both assisted reproductive technologies and subfertility.